Radiosensitivity of Breast Cancer Cells Is Dependent on the Organ Microenvironment - Guo, Genyan; Morse, Ryan T.; Wang, Jie; Chen, Xuan; Zhang, Jiajie; Wang, Andrew Z. (Frontiers in Oncology, 2022)
Background: Distant metastasis is the leading risk factor of death in breast cancer patients, with lung and liver being commonly involved sites of distant seeding. Ongoing clinical trials are studying the benefit from additional local treatment to these metastatic sites with radiation therapy. However, little is known about the tissue-specific microenvironment and the modulating response to treatments due to limitations of traditional in vitro systems. By using biomatrix scaffolds (BMSs) to recreate the complex composition of extracellular matrices in normal organs, we chose to study the radiotherapy response with engineered breast cancer “metastases” in liver and lung organ-specific tissues. Methods: Liver and lung BMSs were prepared for tissue culture. Human breast cancer cell lines were passaged on normal tissue culture plates or tissue culture plates coated with Matrigel, liver BMSs, and lung BMSs. Clonogenic assays were performed to measure cell survival with varying doses of radiation. Reactive Oxygen Species (ROS) detection assay was used to measure ROS levels after 6 Gy irradiation to cancer cells. Results: The response of breast cell lines to varying doses of radiotherapy is affected by their in vitro acellular microenvironment. Breast cancer cells grown in liver BMSs were more radiosensitive than when grown in lung BSMs. ROS levels for breast cancer cells cultured in lung and liver BMSs was higher than that in plastic or in Matrigel plate cells, before and after radiotherapy, highlighting the interaction with surrounding tissue-specific growth factors and cytokines. ROSs in both lung and liver BMSs were significantly increased after radiotherapy delivery, suggesting these sites create prime environments for radiation-induced cell death. Conclusions: The therapeutic response of breast cancer metastases is dependent on the organ-specific microenvironment. The interaction between tissue microenvironment in these organs may identify sensitivity of therapeutic drug targets and radiation delivery for future studies.